2010
DOI: 10.1371/journal.pone.0012516
|View full text |Cite
|
Sign up to set email alerts
|

Linking Power Doppler Ultrasound to the Presence of Th17 Cells in the Rheumatoid Arthritis Joint

Abstract: BackgroundPower Doppler ultrasound (PDUS) is increasingly used to assess synovitis in Rheumatoid Arthritis (RA). Prior studies have shown correlations between PDUS scores and vessel counts, but relationships with T cell immunopathology have not been described.Methodology/Principal FindingsPBMC were isolated from healthy controls (HC) or RA patients and stimulated ex vivo with PMA and ionomycin for 3 hours in the presence of Golgistop. Paired synovial fluid (SF) or synovial tissue (ST) were analysed where avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 51 publications
5
62
0
5
Order By: Relevance
“…+ T cells in peripheral blood, we were unable to demonstrate relationships between active disease (joint counts, ESR, global assessments, CRP or DAS28), in agreement with our previous work [14]. This is in contrast with Leipe et al, who reported a positive correlation between Th17 cells in peripheral blood and CRP in patients with early RA and psoriatic arthritis [3], all of whom were also treatment-naive, but had shorter symptom duration than our cohort.…”
Section: Cd4supporting
confidence: 79%
See 2 more Smart Citations
“…+ T cells in peripheral blood, we were unable to demonstrate relationships between active disease (joint counts, ESR, global assessments, CRP or DAS28), in agreement with our previous work [14]. This is in contrast with Leipe et al, who reported a positive correlation between Th17 cells in peripheral blood and CRP in patients with early RA and psoriatic arthritis [3], all of whom were also treatment-naive, but had shorter symptom duration than our cohort.…”
Section: Cd4supporting
confidence: 79%
“…This study shows that the levels of peripheral IL-17 peripheral blood compared with healthy controls [3,14,[18][19][20][21]. However, conflicting data exist [22,23], including a recent study which showed that patients with early RA within a cohort of EIA had lower levels of Th17 cells [24].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, differences in the genetic background of the two conditions do exist and unique genetic determinants have been identified, although not at genome-wide significance (Liu et al 2008). Nevertheless, PsA shares several key cellular and molecular mediators with psoriasis, such as lymphocytes infiltrating the inflamed skin or joint (Pitzalis et al 1996;Shen et al 2006) and critical cytokines such as tumor necrosis factor (TNF), IL-23, and IL-17 (Gullick et al 2010). Genetic association with class I HLA molecules and clinical evidence supports an important role of CD8 T cells in PsA, with the presence of oligoclonally expanded CD8 T cells in the joint fluids of individuals with active PsA (Costello et al 2001).…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…Increased frequencies of Th17 cells have been observed in the peripheral blood of patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) compared to healthy controls [2,3] and have been shown to be further enriched in synovial fluid from these patients, as well as in synovial tissue from RA and PsA patients, where their levels correlate with systemic inflammation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%